An encounter with scentient beings from Davi Kopenawa´s discourse (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This exhibition tries to understand the cultural forms of communication and mnemic fixation in a specific narrative that Davi Kopenawa, Yanomami shaman, exposes to the anthropologist Bruce Albert, by virtue of Amazonian modes of existence, especially referring to the intensity of jungle spirits and experience Shamanic with spiritual worlds. In the context of a dispersed and outstanding plant extension, we affirm a daily sociability within the framework of a “respectful or loving ethic” among all life forms, aesthetically expressed in significant and transporting forms of emotions developed by Amazonian cosmology. For this we use the notions that Aby Warburg uses in his study of the culture of images, as a course by which they can be understood as living organisms susceptible to transformation, preserving their own biology in the coded transmission of memory.
Keywords: Memory; survival (Nachleben); pathos formula (pathosformeln)